Reproductive outcome of patients undergoing in vitro fertilisation treatment and diagnosed with bacterial vaginosis or abnormal vaginal microbiota: a systematic PRISMA review and meta‐analysis. (25th March 2018) - Haahr, T; Zacho, J; Bräuner, M; Shathmigha, K; Skov Jensen, J; Humaidan, P
Abstract : Background: Despite recent efforts, the risks associated with bacterial vaginosis (BV) or abnormal vaginal microbiota in IVF patients are not well‐established. Objectives: We aimed to evaluate the risks associated with BV in IVF patients using meta‐analysis. Search strategy: Following preliminary searches to find relevant keywords and MeSH terms, a systematic search was performed in PubMed (MEDLINE) in September 2017. Selection criteria: The population was infertile women attending IVF treatment. The exposure was BV or abnormal vaginal microbiota. Outcomes included live birth rate, early spontaneous abortion rate and clinical pregnancy rate. Data collection and analysis: Data were collected for each study and for each outcome using a summary of findings table. If appropriate, data were quantitatively assessed using meta‐analysis, sensitivity analysis, funnel plots and GRADE evidence assessment were performed for the above‐mentioned outcomes. Main results: A total of 12 studies were eligible, comprising a total of 2980 patients. The prevalence of BV was 16% (95% CI 15–18%) in the general study population and tubal factor infertility was highly prevalent in patients diagnosed with BV compared with normal vaginal microbiota patients ( P = 0.001). Despite a significant association with early spontaneous abortion [relative risk (RR) 1.68, 95% CI 1.24–2.27], BV did not significantly impact the live birth rate (RR 1.47, 95% CI 0.96–1.57) or the clinical pregnancy rate (RR 0.93, 95% CI 0.75–1.15). Conclusions: BV is associated with tubal factor infertility and early spontaneous abortion. However, the quality of evidence was very low and the equivocal results justify the need for further research. Tweetable abstract: Abnormal vaginal microbiota is associated with early spontaneous abortion in IVF patients. Tweetable abstract: Abnormal vaginal microbiota is associated with early spontaneous abortion in IVF patients.